Endoplasmic Reticulum Stress Induced Proliferation Remains Intact in Aging Mouse β-Cells - Snyder, Jarin T.; Darko, Christine; Sharma, Rohit B.; Alonso, Laura C. (Frontiers in Endocrinology, 2021)
Aging is associated with loss of proliferation of the insulin-secreting β-cell, a possible contributing factor to the increased prevalence of type 2 diabetes in the elderly. Our group previously discovered that moderate endoplasmic reticulum (ER) stress occurring during glucose exposure increases the adaptive β-cell proliferation response. Specifically, the ATF6α arm of the tripartite Unfolded Protein Response (UPR) promotes β-cell replication in glucose excess conditions. We hypothesized that β-cells from older mice have reduced proliferation due to aberrant UPR signaling or an impaired proliferative response to ER stress or ATF6α activation. To investigate, young and old mouse islet cells were exposed to high glucose with low-dose thapsigargin or activation of overexpressed ATF6α, and β-cell proliferation was quantified by BrdU incorporation. UPR pathway activation was compared by qPCR of target genes and semi-quantitative Xbp1 splicing assay. Intriguingly, although old β-cells had reduced proliferation in high glucose compared to young β-cells, UPR activation and induction of proliferation in response to low-dose thapsigargin or ATF6α activation in high glucose were largely similar between young and old. These results suggest that loss of UPR-led adaptive proliferation does not explain the reduced cell cycle entry in old β-cells, and raise the exciting possibility that future therapies that engage adaptive UPR could increase β-cell number through proliferation even in older individuals.